(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background : Rheumatoid arthritis (RA) is one of the most common autoimmune disorders, affecting approximately 1% of the population worldwide. RA is an inflammatory process in the synovium of the joint that eventually leads to the destruction of both cartilaginous and bony elements of the joint, with resulting pain and disability Aims To study the utility of individualized homeopathic prescription in the planned treatment of rheumatoid arthritis Material and methods: 100 Patients suffering from Rheumatoid arthritis were treated in the OPD of State National Homoeopathic Medical College & Hospital, Lucknow. Analysis& evaluation of symptoms of each case was done after case taking . Patients were prescribed using homoeopathic principles, cases were then assessed with VAS every 15 days & DAS28 Score every 3 months At the end conclusion was drawn on the basis of change in PASI score & DAS 28 score . Descriptive Statistics was used for making inference, Paired t test showed data was statistically significant.